Risk preference and entrepreneurial investment at the top of the wealth distribution - Frank M. Fossen; Johannes König; Carsten Schröder (Empirical Economics, 2023)
We present evidence on how individual risk preferences are related to entrepreneurial investment among the wealthy. To do so, we use novel survey data from the top of the wealth distribution, which have been fully integrated into the 2019 German Socio-economic Panel Study. The data include private wealth balance sheets, in particular the value of own private business assets, and a standard measure of risk tolerance. We find that wealthy individuals are more likely to be entrepreneurs and invest a larger share of their wealth in their own businesses when they are more willing to take risks. A comparison with less wealthy individuals reveals that these associations are stronger among the wealthy. Since the wealthy dominate aggregate risky investment, their extraordinarily high preference for risk and its link to entrepreneurial activity should be taken into account in theory development, empirical analysis, and the design of public policies influencing the riskiness of income and wealth such as progressive taxation.
Keywords: J22; J23; L26; D14; 330; Risk; Wealth; Entrepreneurship; Portfolio choice